Coordination of legislative speech in times of crisis: Youth unemployment and debates on redistributive policies in the Swedish Riksdag, 1994–2014. (27th February 2019) - Bäck, Hanna; Baumann, Markus; Debus, Marc
Abstract : Parliamentary debates and the discussion on different law proposals are a key part of the process of policy making. We argue in this article that a high economic problem pressure in the region an MP represents will affect the MP's legislative speechmaking. We also hypothesise that parties tend to coordinate their speakers in parliament to display a cohesive profile in the domain of labour, employment and immigration issues, i.e., in issue areas which reflect redistributive policies that are highly salient for almost all parties. We evaluate our expectations based on an analysis of Swedish parliamentary debates on labour, employment and immigration policy during the period between 1994 and 2014. The findings show that parliamentary parties coordinate speechmaking: Those MPs who represent economically troubled districts are less likely to appear in plenary debates, as well as MPs who deviate programmatically from the party line.